Quality of life and professional orientation for people with intellectual disability: a case study in Lombardy - Zappella, Emanuela (Form@re - Open Journal per la formazione in rete, 2018)
The concept of quality of life is receiving more attention as a tool for evaluating policies and practices aimed at people with disabilities. This case study describes the process of professional inclusion of Giulia, a girl with Down Syndrome over the last three years of her attendance at a professional school in Northern Italy and the impact that this experience had on her quality of life and on the quality of life of the people who took part in this project. This research intends to: describe the three-year individualized process that lends to the professional inclusion of Giulia in a restaurant; highlight the benefits deriving from work for both oneself and one’s work colleague; emphasise synergies and strategies used in this experience. The paper ends with an analysis of the factors that can favour a positive experience and which can be a starting point for other similar experiences. Qualità della vita e orientamento professionale per le persone con disabilità intellettiva: uno studio di caso in Lombardia Il concetto di qualità della vita sta ricevendo una crescente attenzione come strumento per valutare le politiche e le pratiche rivolte alle persone con disabilità. Questo studio di caso descrive il processo di inclusione professionale di Giulia, una ragazza con Sindrome di Down, durante gli ultimi tre anni di frequenza di una scuola professionale lombarda e l’impatto che questa esperienza ha avuto sulla sua qualità di vita e su quella delle altre persone che hanno preso parte a questo progetto. La ricerca intente: descrivere il percorso individualizzato che ha condotto all’inclusione professionale di Giulia in un ristorante; sottolineare i benefici dell’attività lavorativa sia per lei che per i suoi colleghi; enfatizzare le sinergie e le strategie che hanno caratterizzato questa esperienza. Il lavoro si chiude con un’analisi dei fattori che possono favorire un’esperienza positiva e che possono essere un punto di partenza per altre esperienze simili.